Self-assembling depsipeptide dendrimers and dendritic fullerenes with new cis- and trans-symmetric Hamilton receptor functionalized zn-porphyrins: Synthesis, photophysical properties and cooperativity phenomena - Maurer, Katja; Grimm, Bruno; Wessendorf, Florian; Hartnagel, Kristine; Guldi, Dirk Michael; Hirsch, Andreas (European Journal of Organic Chemistry, 2010)
Two novel supramolecular building blocks, namely cis- and trans-symmetric zinc-porphyrins bearing Hamilton receptors as their focal points (10 and 15), were self-assembled with (i) first-, second- and third-generation depsipeptide cyanurates (21-23); (ii) second-generation dendrofullerene (24), and (iii) cyanuric acid substituted fullerene (20), and probed in a series of photophysical investigations. Importantly, an overall 1:2 stoichiometry was confirmed with binding con-stants Kn, and Hill coefficients nH that indicate remarkable cooperativities. As a general feature, stronger binding evolves from the trans-symmetric porphyrin isomer, although the increased steric demand of the depsipeptide ligands means that the binding constants decrease with each generation. The self-assembly of 10 or 15 with 20 affords novel electron donor-acceptor hybrids that reveal, upon excitation, intra-hybrid charge-transfer events. © 2010 Wiley-VCH Verlag GmbH & Co. KGaA, Weinheim.